ANALISIS STRATEGI BISNIS DAN IMPLEMENTASI DIGITAL MARKETING PADA AMASARI TOURS AND TRAVEL - Muhammad Daffa Irawan; Mochamad Candra Wirawan Arief (Jurnal Pariwisata Tawangmangu, 2026)
Advances in digital technology have prompted tourism companies to adopt appropriate business strategies and leverage digital marketing as a more effective marketing tool. This study aims to analyze the business strategies and digital marketing implementation employed by Amasari Tours and Travel to support sales and business development. The study employed observational, participatory, and on-the-job training methods. Data were collected through field observations, interviews with the director and the operational team, and a review of relevant documentation and literature. Data analysis was conducted descriptively to identify the various business strategies and digital marketing initiatives adopted by the company. The research findings indicate that the business strategies implemented included developing a proposal for cultural tours to Greece and analyzing the potential of tourist destinations in Ciater District, Subang, as part of efforts to create market opportunities and develop tourism products. Meanwhile, digital marketing initiatives included creating a logo and a TikTok account for Hiace Amasari, promoting tour packages via TikTok live streams, and creating an e-flyer promoting tourist destinations in West Java. These various activities demonstrate that a well-planned business strategy and the use of digital media can support promotion, expand market reach, and enhance a company’s competitiveness. Therefore, integrating business strategy and digital marketing is key to ensuring the sustainability of the tour and travel industry in the digital age.